Nuevo concepto de Redacción Periodística. - Aguinaga, Enrique de (Estudios sobre el Mensaje Periodístico, 2000)
A new concept of journalist writing teaching The Author of this article has almost half a century of educational experience on Journalism and, concretely, in the subject of Journalistic Writing whose basis is the accep 307 Enrique de Aguinaga Nuevo concepto de Redacción Periodística tance of the existence of some certain journalistic genres. The Author propound a new concept about the subject of Newswriting or of Journalistic Writing.